2022
DOI: 10.1136/rmdopen-2021-002119
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s and non-Sjögren’s sicca share a similar symptom burden but with a distinct symptom-associated proteomic signature

Abstract: ObjectivesGiven the similarity in symptoms between primary Sjogren’s syndrome (SjS) and non-SjS sicca syndrome (sicca), we sought to characterise clinical and proteomic predictors of symptoms in both groups in order to better understand disease mechanisms and help guide development of immunomodulatory treatments. These have not, to date, unequivocally improved symptoms in SjS clinical trials.MethodsSerum proteomics was performed using O-link inflammation and cardiovascular II panels. SjS (n=53) fulfilled 2016 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In accordance, we previously showed that the transcriptomic profile of plasmacytoid dendritic cells and monocytes of patients with nSS display an intermediate phenotype that largely overlaps with that of patients with pSS 27 28. In addition, patients with nSS also share locally and systemically signs of immune activation with patients with pSS such as presence of effector T cells (Th1, Th17 and Tfh cells) in the salivary glands and similar proteomic profile and increased circulating U6-sncRNA in circulation 29–31. However, differences in IFN signalling and nonsense-mediated decay pathways in cDC2s of patients with nSS could indicate that these patients still maintain some regulatory mechanisms to ensure cellular homeostasis 32.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In accordance, we previously showed that the transcriptomic profile of plasmacytoid dendritic cells and monocytes of patients with nSS display an intermediate phenotype that largely overlaps with that of patients with pSS 27 28. In addition, patients with nSS also share locally and systemically signs of immune activation with patients with pSS such as presence of effector T cells (Th1, Th17 and Tfh cells) in the salivary glands and similar proteomic profile and increased circulating U6-sncRNA in circulation 29–31. However, differences in IFN signalling and nonsense-mediated decay pathways in cDC2s of patients with nSS could indicate that these patients still maintain some regulatory mechanisms to ensure cellular homeostasis 32.…”
Section: Discussionsupporting
confidence: 74%
“…27 28 In addition, patients with nSS also share locally and systemically signs of immune activation with patients with pSS such as presence of effector T cells (Th1, Th17 and Tfh cells) in the salivary glands and similar proteomic profile and increased circulating U6-sncRNA in circulation. [29][30][31] However, differences in IFN signalling and nonsense-mediated decay pathways in cDC2s of patients with nSS could indicate that these patients still maintain some regulatory mechanisms to ensure cellular homeostasis. 32 Altogether, the transcriptional profile of patients with nSS reveals an intermediate phenotype between HCs and patients with pSS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, while xerostomia is a complex condition involving several mechanisms related to salivary glands hypofunction, the correlation between sicca symptoms and salivary flow appears still uncertain, as sicca symptoms can appear even in the presence of preserved salivary flow [48]. As highlighted by previous literature [49][50][51], symptoms burden and qualityof-life impairment between Sjögren's syndrome and sicca syndrome appear similar. Cho et al [49] reported a reduction in quality of life by the same extent in both pSS and sicca patients, despite a difference between groups with regard to clinical symptoms and depression/anxiety.…”
Section: Discussionmentioning
confidence: 94%
“…Such an aspect was confirmed by Chou et al [ 50 ], who highlighted that in symptomatic patients, the presence of a pSS diagnosis corresponded to better emotional and psychological well-being compared to patients without a diagnosis. Finally, Pucino et al [ 51 ] did not report significant differences in terms of quality of life, depression, and anxiety between pSS and sicca patients. Since dryness can occur either in patients affected by pSS or in patients with idiopathic sicca syndrome, according to current evidence, it appears that most of the symptoms could also be ascribed to other factors, including anxiety, depression, and fatigue.…”
Section: Discussionmentioning
confidence: 95%
“…However, there is a lack of correlation between the severity of glandular inflammation and the magnitude of glandular hypofunction [ 15 ]. Moreover, in a group of patients with dry eye and dry mouth defined as non-Sjögren’s sicca syndrome, glandular hypofunction occurs without the presence of organized lymphocytic foci in the salivary glands [ 16 , 17 ]. These observations suggest that multiple immune and non-immune mechanisms must contribute to glandular hypofunction in SjD patients.…”
Section: Introductionmentioning
confidence: 99%